Multimodality imaging with US, CT and MRCP for diagnosing atypical Lemmel syndrome: a case report - Roberto Hernandez-Juarez; Edgar R. Austria-Franco; Mario R. Prada-Bonilla; Asael G. Flores-Mata (Journal of the Mexican Federation of Radiology and Imaging)
Lemmel syndrome is a rare cause of obstructive jaundice caused by extrinsic compression of the common bile duct by a periampullary duodenal diverticulum (PAD). This case report describes Lemmel syndrome in a 71-year-old woman with abdominal pain and jaundice due to a PAD with a completely intradiverticular major papilla. Abdominal ultrasound (US) revealed a distended gallbladder with gallstones and wall thickening with no evidence of an obstructive mass. Computed tomography (CT) revealed a duodenal diverticulum with mixed contents, causing extrinsic compression of the common bile duct. 3.0T magnetic resonance cholangiopancreatography (MRCP) confirmed the intradiverticular location of the biliary and pancreatic ducts. Endoscopic retrograde cholangiopancreatography (ERCP) was performed with sphincterotomy and biliary stenting. The procedure decompressed the biliary tree, resolved the obstruction and inflammatory process, and resulted in a favorable clinical recovery. This presentation is unique due to the intradiverticular location of the biliary and pancreatic ducts with no tumor-related findings. This case report provides diagnostic evidence of a rare anatomic variant, classified as type I Lemmel syndrome according to the both Boix and Li-Tanaka classifications. It highlights the role of non-invasive radiologic techniques in evaluating atypical biliopancreatic disorders. It is reported for educational purposes.